Providing an enabling framework for increasing access to higher education in Nigeria: The evolving role of government (2007)
The ability of a society to produce, select, adapt and utilize knowledge is critical for sustained economic welfare. Hence knowledge gained through the formal education sector has become the most important factor for social and economic development. The Nigerian tertiary education is therefore important if the country is to witness an increase in overall literacy level and general economic development. Except this level of education is solid enough to meet the challenges of producing the needed manpower for the economy, the dream of achieving economic freedom may be difficult. Unfortunately, however, a look at the tertiary education development in Nigeria, particularly at the university level, reveals that the country still lags behind in providing the needed access to its teeming applicants seeking places in its tertiary institutions. In the realization of the important role played by the tertiary institutions and government’s limitations providing for the applicants solely, this paper suggests relevant government policies reform that will enhance greater access to higher education in Nigeria. These policies include, among others, the creation of an enabling environment that will stimulate and encourage expansion in the system